THE IMPACT OF PREOPERATIVE VOLUME OVERLOAD ON HEMODYNAMIC PARAMETERS DURING SHOULDER ARTHROSCOPY - Lyzogub, Kseniia; Lyzogub, Mykola (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2025)
Objective. To investigate the influence of preoperative volemic loading on changes in hemodynamic parameters due to positioning of anesthetized patients in the beach chair position. Methods. A prospective randomized single-center study included 140 patients. Group I (n = 70) — patients who underwent preoperative loading in a volume of 12 ml/kg before changing the body position. Group II (n = 70) — patients who did not undergo preoperative loading. After induction with propofol/fentanyl in standard doses and orotracheal intubation, the patient was transferred from the supine position to the BCP. Non-invasive systolic blood pressure (SBP), diastolic blood pressure (DBP), mean arterial pressure (MAP), and heart rate were determined using a Mediana YM6000 monitor. The first measurement of SBP, DBP, and MAP was performed immediately after positioning the patient supine, the second after induction, the third 5 minutes after positioning in the NSP, and subsequently blood pressure measurements were performed every 5 minutes, heart rate, and SpO2 continuously. In the postoperative period, the following criteria were evaluated: frequency of nausea/vomiting, frequency of orthostatic collapse within 48 hours, average heart rate within 6 hours. Results. Induction of general anesthesia caused comparable changes in hemodynamics in patients of the studied groups without significant differences between groups. When changing the body position in the BCP, hemodynamic changes had significant differences between groups. Only 7.1 % of the subjects in group I had nausea and vomiting in the early postoperative period, while in group II 21.4 % of patients had nausea and vomiting. The development of tachycardia was noted during the first 6 hours after surgery in patients in group II (95.0 ± 5.8), compared with group I (70.3 ± 6.5) (p < 0.001). The development of orthostatic collapse was observed more often in patients in group II and amounted to 14.3 % vs. 10.0 % of the subjects in group I. Conclusions. Preoperative infusion loading does not significantly affect hemodynamic reactions that occur during induction of general anesthesia in young patients ASA I-II. Preoperative infusion loading during operations in a BCP significantly reduces the number of early postoperative complications: postoperative nausea and vomiting, orthostatic collapse and the development of tachycardia.